ASSESSMENT OF THE MAIN ASPECTS OF ENVIRONMENTAL RESPONSIBILITY IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT OF THE ECONOMY OF UKRAINE - Любохинець, Лариса; Мороз, Сергій (SWorldJournal, 2025)
The article considers the role of environmental responsibility of business in the context of ensuring sustainable development of the economy of Ukraine. The theoretical analysis is based on classical and neoclassical approaches to understanding the enviro